Effect of joint configuration on resistance spot weldability of galvanised DP780 steel sheets. (2nd April 2016) - Wei, S. T.; Liu, R. D.; Lv, D.; Lin, L.; Lu, X. F.; Ding, S. W.
Abstract : A 780 MPa galvanised dual phase (DP) steel was two-, three- and four-layer resistance spot welded under different welding parameters and joint configurations. The splash situation, nugget sizes and tensile shear properties of the spot welds were evaluated systematically. The results showed that the splash occurring current increased in the order of two-, three- and four-layer spot welds owing to the increasing metal volume for melting. The joint configuration had a great influence on the tensile shear properties of the spot welds. The three- and four-layer spot welds with proper joint configurations had better weld quality than the two-layer spot weld. Therefore, well designed multilayer spot welds could be used to replace the commonly used two-layer spot welds in actual production.